Implementation of metanoia - shift of mind in shaping the character of members of the Indonesian police criminal and investigation organization (Bareskrim Polri) - Hartanto, Dadang (Penerbit Universiti Kebangsaan Malaysia, 2021)
The purpose of this study was to analyze the implementation of metanoia - shift of mind in shaping the character of organizational members (Bareskrim Polri). The type of research that researchers do is qualitative research. The data was collected by means of interviews and focus group discussions, but research was also carried out in the sociological field to strengthen this research. Furthermore, the data analysis process is carried out in order to arrange the data obtained into a category or a basic description of the field study by reducing, presenting data and drawing conclusions. The results of this study found that through a new perspective, someone increasingly understands the reality faced in order to create the reality that the National Criminal Investigation Unit wants to show that it produces a change of thought (metanoia or new mind set) at Bareskrim which is marked by the achievement of four conditions: loyalty, creativity, integrity, competence of organizational members at Bareskrim. First, loyalty, namely loyalty and willingness of organizational members to realize a common vision. Second, honesty and commitment of members of the organization not to abuse their authority for personal interests that are against the expectations of society. Third, the ability to master and carry out work is faced with changing environments that develop complex and dynamic. Fourth, namely the ability to systematically describe the various problems faced as current realities then determine decisions, actions and implement ideas or innovations that can realize the expected reality (vision).